Beta-Lactamases in a Tertiary Care Hospital: "Biological Quake" Knocking at the Door - Sapkota, Gyanendra; Yadav, Santosh Kumar; Adhikari, Samaj; Lakhey, Mamta; Mishra, Shyam Kumar (Journal of Karnali Academy of Health Sciences, 2021)
Background: Antimicrobial resistance due to the production of extended-spectrum β-lactamases (ESBLs), AmpC β-lactamases, and metallo-β-lactamases (MBLs) have emerged as a major health catastrophe limiting antibiotic treatment options. Therefore, this study was conducted to assess the current level of ESBLs, AmpC β-lactamases, and MBLs- producing bacteria and their antibiotic susceptibility profile in a Nepalese hospital. Methods: This cross-sectional study was carried out among the inpatients of Medicare National Hospital, Kathmandu from April to September 2015. During the study period, a total of 589 specimens (urine, sputum, blood, pus, body fluids, throat swab, central venous catheter - CVC tip) collected aseptically from the admitted patients were selected in the study. The collected specimens were processed, and the isolated organisms were identified following the standard microbiological methods. ESBL was detected by standard combination disc method and double-disc synergy test. Tests for AmpC and co-production of ESBL and AmpC were done by using MASTDISCSTM ID AmpC and ESBL Detection Discs, and ESBL and AmpC detection Ezy MICTM Strip. The Imipenem-EDTA combination disc method was done for the identification of MBL in Gram-negative bacteria. Results: Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Enterococcus faecalis, and Candida albicans were the common microbial agents isolated from hospital-admitted patients. Among total 84 Gram-negative bacteria tested for ESBL-production; 23 (27.4%) isolates were ESBL-producers. ESBL production was seen in 32.3% of Escherichia coli and 28.6% of Klebsiella pneumoniae isolates. Similarly, MBL production was identified in 28.6% of Pseudomonas aeruginosa, and 6.5% of Escherichia coli. Likewise, 3.2% of Escherichia coli were AmpC β-lactamase-producers. The ESBL-producing bacteria showed less susceptibility to different antibiotics as compared to non-ESBL-producers. Consistent results were found with different methods like combination disk method, MASTDISKSTM ID AmpC and ESBL disk, Ezy MICTM Strip (MIX+/MIX) method, and triple ESBL detection Ezy MICTM strips employed for the detection of ESBL and AmpC. Conclusions: ESBL was commonly seen in Escherichia coli while MBL in Pseudomonas aeruginosa. Routine monitoring of these kinds of resistance phenotypes following appropriate methods is essential for the proper treatment of patients.